A comparative analysis of stereotypes between Romania and the Republic of Moldova - Călin, Mariana Floricica; Tasențe, Tănase; Martinescu, Octavian (Technium Social Sciences Journal, 2022)
One of the current research themes, in the society we are part of, is the theme of stereotypes. Regardless of nationality, gender, faith, age, etc., people tend to judge or categorize those around them. In labeling, we don't think about what long-term effects can occur, in fact we don't think rationally when it comes to "gossip" on someone. Later, some have remorse, others feel nothing, but everything has a double meaning. Today you subject someone to prejudice, tomorrow you can be the main topic of a discussion. We are the generation of the 21st century, the century of movement and agitation. It is well known that we are rapidly modernizing technologically, we have a wider openness to learn things easily, we have the capacity and the necessary resources to create something special, something special. Even if all these things are available to us, we can, however, notice that man adapts more difficult to new changes, even more, he cannot forget old habits. Since we know the more modernized and cultured man, we notice that he is guided in society by certain criteria and false-moderate knowledge from the past. Thus, in this truly amazing era, we humans are subjected to discriminations and stereotypes long forgotten in the history of our formation.